2022
DOI: 10.3390/nu14224808
|View full text |Cite
|
Sign up to set email alerts
|

Mulberry Leaf (Morus alba L.) Extracts and Its Chlorogenic Acid Isomer Component Improve Glucolipotoxicity-Induced Hepatic Lipid Accumulation via Downregulating miR-34a and Decreased Inflammation

Abstract: Mulberry leaf (Morus alba L.) is used as a traditional medicine and potential health food to treat various metabolic diseases, such as hypertension, diabetes, and hyperlipidemia. However, we sought the mechanisms by which functional components of mulberry leaves mediate diabetic steatohepatitis. We applied an in vitro model of HepG2 cells induced by glucolipotoxicity and evaluated the effects of MLE and its major components nCGA, Crp, and CGA. The results showed that MLE and nCGA reduced liver fat accumulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…SREBP-1c is the main transcriptional regulator of FASN and plays a critical role in lipogenesis. This result is consistent with those of previous reports on the use of mulberry leaves to alleviate nonalcoholic fatty liver disease ( Yang et al, 2022 ). FDFT1 and HMGCR play central roles in cholesterol synthesis ( Chen et al, 2023 ).…”
Section: Discussionsupporting
confidence: 94%
“…SREBP-1c is the main transcriptional regulator of FASN and plays a critical role in lipogenesis. This result is consistent with those of previous reports on the use of mulberry leaves to alleviate nonalcoholic fatty liver disease ( Yang et al, 2022 ). FDFT1 and HMGCR play central roles in cholesterol synthesis ( Chen et al, 2023 ).…”
Section: Discussionsupporting
confidence: 94%
“…The main isomers of CGA and nCGA are found in MLE. 24 However, the mechanism through which MLE ameliorates DN and what role nCGA plays in this process remain unclear. The present study investigated the effects of MLE and its main compound nCGA on kidney fibrosis, inflammation, and oxidative stress in a glucolipotoxicity-induced Lepr db diabetic (db/ db) mouse model.…”
Section: Introductionmentioning
confidence: 99%
“…Yuan et al found that rutin in mulberry leaf flavonoid compounds could increase the number of mitochondria in brown adipocytes by upregulating the expression of UCP1, thereby increasing energy expenditure (Yuan et al, 2017). For mulberry leaf polyphenols, as one of the main components of mulberry leaf polyphenols, Yang et al found that chlorogenic acid may reduce fat accumulation by inhibiting SREBP‐1/FASN, SREBP‐2/MMG‐CoaR and activating PPARα/CPT‐1 (Yang et al, 2022). Subsequently, Zeni ALB et al found that phenols in mulberry leaves can inhibit the content of TC, TG and VLDL‐C in serum, and increase the content of HDL‐C (Zeni et al, 2017).…”
Section: Discussionmentioning
confidence: 99%